The School Bus Symposium: A Poetic Journey of Co-created Conference Space - Mitchell A McLarnon (Art/Research International, 2016)
With the intention of disrupting and re-imagining traditional conference spaces, this article is a poetic compilation developed from a Curriculum Studies conference symposium that took place on a school bus. During the School Bus Symposium, in situ poetry writing and reading, song and storytelling occurred in response to open ended prompts and facilitation of creative activities. After the symposium, a call was issued to invite participants to submit any poetry or stories produced during, or inspired by the session. Consisting of 18 submissions including poetry, story, photography and creative essays, infused by curriculum theory and poetic inquiry, this collection offers an inclusive, reflective, participatory, and experiential rendering where participants are living and journeying poetically. Emphasizing creative engagement with personal memories, the authors collectively aimed to promote art education through imaginative approaches to curriculum studies, poetic inquiry and academic conferences.